(untitled) (International Journal of Nursing Education, 2020)
Introduction: Organ donation is the process of surgically removing an organ or tissue from one person (theorgan donor) and placing it into another person (the recipient). The study was conducted in urban and ruralcommunities of Delhi to assess the knowledge and attitude of general population towards organ donation.Methodology: Quantitative approach and cross -sectional study design was used for conducting the study.Purposive non-probability sampling technique was adopted to select the communities and the sample andthe sample size was 1089. Structured knowledge and attitude interview schedules were used to assess theknowledge and attitude respectively regarding organ donation. Data was collected in home settings frompeople above 18 years of age. Data was collected regarding background variables of study subjects and theirknowledge and attitude regarding organ donation.Result: Sample characteristics revealed that 59.5% of respondents were females, 64%) were in the age groupof 18 to 35 years, 84.7% followed Hindu religion and 63.6% were educated up to secondary level or above.Majority of subjects (78.6%) were aware that organ can be donated to save life of another person, while38.8% subjects knew that organs can be donated both during life and after death. Majority of subjects wereaware that only eyes (76.7%) and kidney (63.5%) can be donated. Overall about 10.8% had good knowledgeand 55.5% had average knowledge about organ donation. Age, gender and education had statically significantassociation with knowledge regarding organ donation with p-value less than 0.05. Majority (83.2%) had inappropriate attitude towards organ donation. Statistically there was no significant association between levelof attitude with background variables namely age, gender, religion and education.Conclusion: The findings of study revealed that general population had average knowledge about the organdonation, but inappropriate attitude towards organ donation